Cytotoxicity and electron microscopy of cell death induced by goniothalamin - Ali, A.; McKeen, M.; Hamid, M.; Aun, Q.; Zauyah, Y.; Azimahtol, H.; Kawazu, K. (Georg Thieme Verlag KG, 1997)
The cytotoxicity of goniothalamin was found to be strong towards both cancerous (HGC-27, MCF-7, PANC-1, HeLa), and non-cancerous (3T3) cell lines, especially in cases of dividing cells. Drug exposure studies indicated that the cytotoxic action of goniothalamin was time- and dose-dependent. At the ultra-structural level, goniothalamin-induced cytotoxicity revealed a necrotic mode of cell death towards MCF-7 cells.